Vliianie sem'i uchashchegosia s invalidnost'iu na formirovanie motivatsii k polucheniiu vysshego obrazovaniia - Chapala I. A. (Socio-Cultural and Psychological Problems of the Modern Family: Current Issues of Assistance and Support, 2022)
The article examines the dependence of the parental position in relation to their child with developmental disabilities and their higher education. The question of motivation for obtaining higher education by people with developmental problems themselves is touched upon.
Keywords: высшее образование; вуз; семья; higher education; university; студенты с инвалидностью; family; students with disabilities